(untitled) - Speser, Phyllis L. (Hoboken, N.J., 2006)
This readable book is a must for anyone wanting to look at the technology transfer process from a novel viewpoint. Rather than just recite the nuts and bolts of the process, it illustrates theoretical concepts with real world, practical examples. Any reader will come away with new and useful ways of looking at, and doing, this business.
Keywords: Technology transfer,Chuyển giao công nghệ